Effect of environmental exposure on autogenous self-healing of cracked cement-based materials. (September 2018) - Suleiman, A.R.; Nehdi, M.L.
Abstract: Despite abundant literature on self-healing of cement-based materials, there is dearth of information on how environmental exposure affects self-healing. In this study, self-healing of cracks in cement mortar under different environmental exposure was investigated. Pre-cracked mortar specimens were submerged in water, while identical specimens were exposed to cyclic temperature and relative humidity. Change in crack width was examined using optical microscopy. SEM coupled with energy dispersive X-ray analysis was used to identify healing compounds. Mercury Intrusion Porosimetry, water absorption and permeability were employed to assess porosity. X-ray computed tomography was deployed to explore healing of internal cracks. No significant self-healing occurred in specimens exposed to cyclic T and RH. Although crack self-healing was identified in submerged specimens, X-ray μCT demonstrated that it was limited to exposed surface of specimens. This warrants further research to bridge the gap between laboratory findings on self-healing and actual field performance of ageing civil infrastructure.